2015
DOI: 10.2106/jbjs.n.00992
|View full text |Cite
|
Sign up to set email alerts
|

Chondroblastoma of Bone in the Extremities

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
155
7
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(184 citation statements)
references
References 35 publications
18
155
7
4
Order By: Relevance
“…Overall, our results correspond to published data of the literature [7]: showing a clear male predominance (1:2.7), presenting with pain in most of the patients [2,3,8,12,19]. The most frequent tumor site was the femur, followed by the humerus and the tibia affecting more frequently the proximal meta-epiphyseal region [6].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, our results correspond to published data of the literature [7]: showing a clear male predominance (1:2.7), presenting with pain in most of the patients [2,3,8,12,19]. The most frequent tumor site was the femur, followed by the humerus and the tibia affecting more frequently the proximal meta-epiphyseal region [6].…”
Section: Discussionsupporting
confidence: 89%
“…The additional use of phenol in cases of concomitant aneurysmal bone cysts is helpful in the avoidance of recurrence, even though the significance of secondary cysts also lacks unanimous answer. However, in a recent multi-centre study, Xu et al [9,12] showed curettage and bone grafting to provide favorable local control and satisfactory functional outcome for patients with chondroblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggressive curettage remains the mainstay of treatment for chondroblastoma of bone, because it is associated with a low likelihood of metastases and local recurrences [24,26]. However, considering that this epiphyseal tumor affects primarily children and young adults, the question arises whether this treatment approach also results in durable preservation of the patient's native articular surface over the years after the initial treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is about 1.45% of all primary bone tumors . CB usually affects the epiphyses of long bones, in young patients . Histologically, CB usually features diffuse proliferation of mononuclear round cells, often with cleaved nuclei, and pink “immature” cartilage islands.…”
mentioning
confidence: 99%